The effects of unemployment on gambling behaviour in Iceland: Are gambling rates higher in unemployed populations? - Eilif Magnusson Arge 1991-; Steinþór Kristjánsson 1986- (2015)
Prentað eintak barst ekki til Landsbókasafns Íslands - Háskólabókasafns. The aim of this study is to shed a light on the effects of employment status on gambling behaviour, with relation to problem gambling. The handful of previous studies on the subject have not found any consistent association between unemployment and gambling behaviour. However, none of these studies have had employment status in relation to gambling as their main focus. This lack of research in the field calls for further research and the study at hand was made in light of this paucity of previous research on the subject. The current study used a simple random sample of 1887 participants from Registers Iceland used in an Icelandic population survey in 2011. The age of the participants varied from 18-70 years with the mean age being 41.5 years (SD = 14.5 years). The data was gathered through telephone using a 180 question survey which covered several background variables and an extensive number of questions concerning gambling. The first objective was to see whether unemployment relates to gambling patterns. The second objective was to reveal whether EGM gambling is more prevalent among those who are unemployed than amongst those who are employed or in school. The third and final objective was to see whether problem gamblers were more likely to be unemployed than employed or in school. None of the objectives were fully supported in this study. Unemployment was found to have a quite weak and inconsistent association to gambling patterns. Significant effect sizes varied between gambling types from -0.05 to -0.07 while 7 of 12 gambling types showed a non-significant association with unemployment. The second objective was not supported as EGM gambling was not more prevalent among those unemployed. The third objective was also not supported as problem gambling was not found to be associated with employment status. The results indicate that unemployment is in little or no way associated with gambling patterns, that EGM gambling is not more ...